Solitons in affine Toda field theories - Timothy Hollowood (Nuclear Physics B, 1992)
The solutions of classical A r affine Toda field theories, with imaginary coupling constant, are investigated. Soliton solutions are found, which, despite the complex form of the hamiltonian, have real classical masses. The solitons have the same gross spectrum as the fundamental Toda particles, although in addition to their mass they carry a non-trivial topological charge, which is a weight of one of the fundamental representations of A r . Multiple-soliton solutions are constructed which describe the classical scattering theory of the solitons. The generalization to other simply laced theories is briefly considered, with some explicit results forD 4